OP0326 RADIOGRAPHIC AND PAIN OUTCOMES FROM A PHASE 3 EXTENSION STUDY (OA-07) EVALUATING THE SAFETY AND EFFICACY OF REPEAT LORECIVIVINT INJECTIONS OVER 3 YEARS IN SUBJECTS WITH SEVERE KNEE OSTEOARTHRITIS - Yazici, Y.; Swearingen, C.; Tambiah, J. R. S.; Mcalindon, T. (Annals of the rheumatic diseases, 2024)
Background:Knee osteoarthritis (OA) has an unmet need for safe and efficacious symptom and disease-modifying treatments. Lorecivivint (LOR), an intra-articular (IA) CLK/DYRK inhibitor thought to modulate Wnt and inflammatory pathways has previously appeared safe, improved patient-reported outcomes (PROs) and maintained radiographic medial joint space width (JSW) compared with placebo (PBO). A Phase 3 extension study, OA-07 (NCT04520607), evaluated LOR safety and efficacy with outcomes of medial JSW (mm), WOMAC Pain [0-100], and WOMAC Function [0-100].Objectives:To evaluate efficacy and safety of long-term, repeated usage of LOR in patients with severe knee OA.Methods:Patients had advanced knee OA (medial JSW 1.5-4 mm) and completed the 1-year parent Phase 3 trial (OA-11, NCT 03928184). A repeat injection according to the parent trial randomization (LOR/ PBO) was given at the beginning of the single-blind (participants and investigators) extension Year 1. At the beginning of Year 2, all participants received a third injection of LOR 0.07 mg and entered a crossover open-label phase (still blinded to original treatment). Baseline-adjusted ANCOVA estimated differences between LOR and PBO outcomes using OA-07 baseline measures. Treatment effect at Month 36 was estimated using marginal comparison from baseline adjusted ANCOVA to last PBO observation prior to crossover.Results:276 patients (mean age 61.0 ± 8.2 years, BMI (Body Mass Index) 31.8 ± 4.9 kg/m2, female 62.7%, KL3 45.3%, medial JSW 2.63 ± 0.69 mm, 67.4% bilaterally symptomatic, 68.5% medial JSW < 3 mm) were enrolled. LOR appeared safe and well-tolerated with no major adverse event rate differences to PBO.Comparing LOR to PBO in Full Analysis Set (FAS) completers:At 24 months, LOR showed numerically less medial JSW loss: LOR -0.11 (± 0.05) mm vs. PBO -0.20 (± 0.05) mm (Δ=0.09 mm, 95% CI [-0.06, 0.23], P=0.223) (Figure 1). LOR improvements were observed for WOMAC Pain Δ=-5.18 (95% CI [-10.28, -0.08], P=0.047) (Figure 2a) and WOMAC Function Δ=-4.90 (95% CI [-9.92, 0.13], P=0.056) (Figure 2b).At 36 months, LOR showed numerically less medial JSW loss, compared to pre-crossover PBO measure, -0.06 (± 0.08) mm, (Δ=0.15 mm, P=0.045)Comparing LOR to PBO in KL2 FAS completers:At 24 months, LOR showed numerically less medial JSW loss: LOR 0.00 (± 0.06) mm (n=38) vs. PBO -0.08 (± 0.06) mm (n=45) (Δ=0.08 mm, 95% CI [-0.09, 0.26], P=0.354).At 36 months, LOR showed improved medial JSW, compared to pre-crossover PBO measure, 0.17 (± 0.11) mm, (Δ=0.29 mm, P=0.012)Conclusion:In this advanced knee OA cohort, LOR 0.07 mg appeared safe and OA-07 met its primary objective with repeat LOR injections showing medial JSW improvement compared to PBO after 3 years (3 injections). Beneficial LOR effects compared to PBO were also seen across pain and function PROs and were more pronounced in KL2 patients. PBO patients who crossed to LOR treatment showed similar benefits after 12 months, providing further evidence of potential efficacy. LOR continues to show promise as a safe, disease-modifying knee OA treatment.REFERENCES:NIL.Figure 1.Change in Medial Joint Space Width in OA-07 from OA-11 BaselineFigure 2.Change in WOMAC (a) Pain and (b) Function in OA-07 from OA-07 BaselineAcknowledgements:NIL.Disclosure of Interests:Yusuf Yazici Biosplice Therapeutics, Christopher Swearingen Biosplice Therapeutics, Jeyanesh R S Tambiah Biosplice Therapeutics, Timothy McAlindon: None declared.